Triterpenic saponins as regulator of plant growth - S. Saha; S. Walia; J. Kumar; B. S. Parmar (Journal of Applied Botany and Food Quality, 2012)
To investigate the plant growth regulatory effect of saponins, two bisdesmosidic triterpenic saponins with hederagenin and l6-α-hydroxy protobassic acid as an aglycon were isolated from Sapindus mukorossi Gaertn (Family: Sapindeae) and Diploknema butyracea (Family: Sapotaceae). Two triterpenoids were applied on the rice and maize seeds for germination and growth regulation tests. We concluded the following. l6-α-hydroxy protobassic acid glycosides had a growth promoting activity in maize and rice. The effect was more prominent in maize than in rice. Whereas, hederagenin glycoside had a slight growth inhibitory effect on rice. The saponin showed growth promoting activity in maize below 250 µg ml-1. In general, hederagenin glycoside showed root growth inhibiting effect in rice and 16-α-hydroxy protobassic acid glycosides had pro motive effects on the entire plant of rice and maize at low concentration. These active compounds from D. butyracea could be further exploited as potential plant growth regulators in agricultural applications in the future.